Encapsulation of Nigella sativa L. essential oil into liposomes using supercritical carbon dioxide: Process optimization and enhancement of encapsulation efficiency and efficacy of bioactive components - Dar, Ishfaq Hamid; Junaid, Pir Mohammad; Ahmad , Saghir (Journal of Postharvest Technology, 2022)
The Nigella sativa essential oil has been shown to possess a number of nutritional and medicinal benefits to the human body. Most of the  bioactive compounds in it are heat sensitive and degrade during processing and storage. In order to improve their desirability and extend storability of these bioactive agents, encapsulation of Nigella sativa essential oil into liposomes was carried out using supercritical carbon  dioxide by the rapid expansion of supercritical solution (RESS) process. This study was aimed at evaluating the effect of different process  variables viz. Pressure, temperature and oil-to-lipid ratio on encapsulation efficiency, particle size distribution and stability of resulting  encapsulates. Numerical optimization of process parameters suggested that the optimum conditions for the encapsulation process were  pressure of 390 bar, temperature of 40°C and oil-to-lipid ratio of 7.6. Under these conditions maximum encapsulation efficiency of 88 percent  was achieved with a mean particle diameter of 173 nm and a uniform size distribution (polydispersity Index of 0.30) with fair stability (zeta  potential of -57mV). The results signified the encapsulation process using supercritical carbon dioxide by RESS method as a viable alternative  for the sensitive bioactive components in Nigella sativa essential oil.
Keywords: Encapsulation; bioactive components; supercritical carbon dioxide